2020
DOI: 10.1080/20013078.2020.1761072
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicles modulated by αVβ3 integrin induce neuroendocrine differentiation in recipient cancer cells

Abstract: The ability of small extracellular vesicles (sEVs) to reprogram cancer cells is well established. However, the specific sEV components able to mediate aberrant effects in cancer cells have not been characterized. Integrins are major players in mediating sEV functions. We have previously reported that the αVβ3 integrin is detected in sEVs of prostate cancer (PrCa) cells and transferred into recipient cells. Here, we investigate whether sEVs from αVβ3-expressing cells affect tumour growth differently than sEVs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 53 publications
4
38
0
Order By: Relevance
“…We can speculate that upon RB1 loss, downregulation of αVβ6 and gain of the αVβ3 integrin are required in the primary tumors in the early stages of NED to confer upon NEPrCa the ability to metastasize in different sites ( Fig 6 ). Upon metastasizing, the αVβ3 integrin expression is sustained as shown here and as previously described [ 7 ] in NEPrCa bone metastasis, indicating additional pro-survival functions provided by this integrin.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…We can speculate that upon RB1 loss, downregulation of αVβ6 and gain of the αVβ3 integrin are required in the primary tumors in the early stages of NED to confer upon NEPrCa the ability to metastasize in different sites ( Fig 6 ). Upon metastasizing, the αVβ3 integrin expression is sustained as shown here and as previously described [ 7 ] in NEPrCa bone metastasis, indicating additional pro-survival functions provided by this integrin.…”
Section: Discussionsupporting
confidence: 86%
“…In a recent study, we have shown that the αVβ3 integrin is found in small extracellular vesicles released by cancer cells and that small extracellular vesicles containing αVβ3 have a unique ability to promote NED of PrCa in vivo [ 7 ]. Based on these findings, we hypothesized that elevated expression levels of αVβ3 might correlate with NED in PrCa.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations